On screen acting an introduction to the art of acting for the screen - Dmytryk, Edward; Dmytryk, Jean Porter (Routledge, Taylor & Francis Group, 2019)
"With On Screen Acting, director Edward Dmytryk and actress Jean Porter Dmytryk offer a lively dialogue between director and actress about the principles and practice of screen acting for film and television. Informal and anecdotal in style, the book spans auditioning, casting, rehearsal, and on-set techniques, and will be of interest to both aspiring and working actors and directors. Originally published in 1984, this reissue of Dmytryk's classic acting book includes a new critical introduction by Paul Thompson, as well as chapter lessons, discussion questions, exercises, and a glossary"--